The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0103932
|View full text |Cite
|
Sign up to set email alerts
|

Cascade Bioassay Evidence for the Existence of Urothelium-Derived Inhibitory Factor in Guinea Pig Urinary Bladder

Abstract: Our aim was to investigate whether guinea pig urothelium-derived bioactivities compatible with the existence of urothelium-derived inhibitory factor could be demonstrated by in vitro serial bioassay and whether purinergic P1 receptor agonists, nitric oxide, nitrite or prostaglandins might explain observed activities. In a cascade superfusion system, urothelium-denuded guinea pig ureters were used as bioassay tissues, recording their spontaneous rhythmic contractions in presence of scopolamine. Urothelium-intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…Hawthorn et al reported smaller carbachol‐evoked contractions in intact strips of pig bladder compared with mucosa‐free strips; moreover, mucosa‐free strip contractions were inhibited by the presence of a second intact strip indicating release of a modulatory signal. The exact identity of this diffusible UDIF is not yet known although several candidates have been proposed and excluded …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hawthorn et al reported smaller carbachol‐evoked contractions in intact strips of pig bladder compared with mucosa‐free strips; moreover, mucosa‐free strip contractions were inhibited by the presence of a second intact strip indicating release of a modulatory signal. The exact identity of this diffusible UDIF is not yet known although several candidates have been proposed and excluded …”
Section: Introductionmentioning
confidence: 99%
“…The exact identity of this diffusible UDIF is not yet known although several candidates have been proposed and excluded. 8 Botulinum toxin type A (BoNT-A) is used to treat antimuscarinic refractory detrusor overactivity (DO) where involuntary detrusor contractions can be observed and overactive bladder syndrome (OAB) where DO may or may not be demonstrable. 9 The established mechanism of action of BoNT-A on neurones involves cleavage of synaptosome-associated protein-25 (SNAP-25), a component of the neuronal SNARE complex, preventing neuronal transmitter release.…”
mentioning
confidence: 99%
“…There was also a tendency to higher force development in response to carbachol, but this difference did not reach statistical significance. These results suggest that endogenous NO may attenuate the level of stimulated tension development [3] and confirm that NO is probably not the urothelium-derived relaxing factor [4,25,26]. Moreover, NO is unlikely to be involved in noradrenaline-induced relaxation because L-NAME had no effect on the concentration-relaxation curves with or without urothelium.…”
Section: Discussionmentioning
confidence: 59%
“…The study using human bladder strips showed that the factor was distinct from nitric oxide and it persisted in the presence of beta‐adrenoceptor blockade or cyclooxygenase inhibition. The existence of the urothelium‐derived inhibitory factor in the guinea pig urinary bladder was also demonstrated by assay on the spontaneous contracted guinea pig ureters in a cascade superfusion bioassay system, which offers further possibilities to identify the factor . The results indicated a transmissible inhibitory factor over a significant distance and seemed less likely to be nitric oxide, nitrite, an adenosine receptor agonist or cyclooxygenase products.…”
Section: Urothelium Released Unknown Inhibitory Factor(s)mentioning
confidence: 94%